2017
DOI: 10.1002/2017gl073777
|View full text |Cite
|
Sign up to set email alerts
|

The coastal mean dynamic topography in Norway observed by CryoSat‐2 and GOCE

Abstract: New‐generation synthetic aperture radar altimetry, as implemented on CryoSat‐2, observes sea surface heights in coastal areas that were previously not monitored by conventional altimetry. Therefore, CryoSat‐2 is expected to improve the coastal mean dynamic topography (MDT). However, the MDT remains highly reliant on the geoid. Using new regional geoid models as well as CryoSat‐2 data, we determine three geodetic coastal MDT models in Norway and validate them against independent tide‐gauge observations and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
4
20
0
1
Order By: Relevance
“…Finally, our values are comparable to estimates from, e.g., Ophaug et al (2015) and Idžanović et al (2017) along the Norwegian coast and Lin et al (2015) along the Pacific coasts of Japan and North America. Although there may be correlation among some of the ocean models, they generally appear to provide errors of a similar magnitude, or less, than those from the geoid models at the tide gauge locations (Fig.…”
Section: Discussion Of Australian Mdt Profilessupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, our values are comparable to estimates from, e.g., Ophaug et al (2015) and Idžanović et al (2017) along the Norwegian coast and Lin et al (2015) along the Pacific coasts of Japan and North America. Although there may be correlation among some of the ocean models, they generally appear to provide errors of a similar magnitude, or less, than those from the geoid models at the tide gauge locations (Fig.…”
Section: Discussion Of Australian Mdt Profilessupporting
confidence: 88%
“…However, the comparisons conducted in Section 3 do go some way to providing upper and lower bounds. Previous studies around Australia (Featherstone and Filmer 2012;Filmer 2014) and in other regions (Woodworth et al 2012;Hughes et al 2015;Lin et al 2015;Ophaug et al 2015;Higginson et al 2015;Mazloff et al 2014;Idžanović et al 2017) found standard deviation (SD) of differences among MDT models ranging from ~±30 mm to ~±80 mm. The resolution-induced (omission) errors discussed above are subsumed within these SDs, but will vary depending on the spatial resolution of the different models (Table 1).…”
Section: Mdt Errors At Australian Tide Gaugesmentioning
confidence: 99%
“…This can be done through the integration with very highresolution ocean model. Local analysis into the Norwegian MDT demonstrated the value of SAR altimetry in mapping local coastal topographies from CryoSat-2 (Idžanović et al, 2017). Along the Norwegian coast strong levelling ties between tide gauges permit a comparison, which is not dependent on direct GPS measurements at each gauge.…”
Section: Discussion Recommendations and Conclusionmentioning
confidence: 99%
“…Frequently, regional geoid models are extended over oceans as a by-product. When the marine gravity data come from terrestrial gravity measurements (as opposed to altimetry), the resulting geoid models are suitable for determining the coastal MDT (Higginson et al, 2015;Hipkin, 2000;Idžanović et al, 2017;Lin et al, 2015;Ophaug et al, 2015). Otherwise, caution must be taken in the interpretation of the resulting MDT.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%